(untitled) (Italian Review of Legal History, 2015)
The provisions of the Constitutio Criminalis Carolina on the intervention of the defending counsel in the trial seemed to be less strict than other contemporary European criminal rules. Since the 16th century the criminal law scholars from the German area read them on the one hand connoting the lawyer with increasing precision as an expert in law, on the other one limiting his leeway in order to not hinder the rapidity and effectiveness of the inquisitio. This perspective influenced the choices of the Austrian legislators, which were even toughened from the 18th century onwards in the work of legislative unification by Maria Theresia and in the following codes.